The implementation of the choice on termination of pregnancy act: some empirical findings - MC Engelbrecht; AJ Pelser; Charles Ngwena; HCJ van Rensburg (AOSIS, 2000)
The Choice on Termination o f Pregnancy Act o f 1996substantially liberalised abortion law. Whilst a substantial number of terminations of pregnancies (TOPs) have already been performed in terms of the new Act, it has also surfaced that an array of factors of various kinds may impede its further implementation and operation. A study was undertaken to determine the nature and extent of any such impediments to the implementation of the Choice on Termination o f Pregnancy Act. More specifically a survey was conducted amongst a sample of 75 women who had undergone a TOP since the implementation of the Act; health professionals and social workers who provide TOP services (n=16); and health professionals and social workers who are in a position to refer women to TOP facilities (n=63). Overall, the clients were well treated at the TOP facilities, and were satisfied with the service given to them. However, post-counselling and to a lesser extent pre-counselling, is lacking. Counselling is important as a considerable proportion of the clients suffered from emotional feelings usually associated with depression and/or self-reproach before and after the termination procedure. Furthermore these clients did not usually discuss their termination with family members. TOP service providers were dissatisfied with the TOP facilities, especially the insufficient number of consultation and counselling rooms. Health care workers in a position to refer clients to TOP facilities were not always willing to do so, thereby obstructing the referral system. In the main, it is recommended that the entire TOP procedure should be done at clinics/hospitals so that clients will not have to do inductions at home, more trained staff should be available, facilities should be adequate and accessible, and there should be psychological support for staff.